Saccharin analysis in pharmaceutical and cosmetic preparations by derivative ultraviolet spectrophotometry (Revista Brasileira de Ciências Farmacêuticas, 2002)
Saccharin, a synthetic sweetener constituent of several pharmaceutical and cosmetic preparations, is analyzed qualitatively and quantitatively in the presence of interferences like active ingredients and excipients. A derivative ultraviolet spectrophotometric method employing the second and the fourth orders was used. The calibration data obtained were satisfactory, with a relative precision range of 0.53%-0.72%, and linearity between 0.9998-0.9999. The recovery test results for the toothgel sample ranged between 97.80% and 104.95% in the second order of derivative and between 98.04% and 101.32% in the fourth derivative, respectively, using zero-peak (ZP) and peak-peak (PP) methods. The suspension sample showed values between 97.35% and 104.72% in the second derivative and between 95.94% to 104.41% in the fourth derivative, respectively, employing the zero-peak (ZP) and peak-peak (PP) methods. The proposed method showed precision, accuracy and simplicity.